Can an innovation platform support a local process of climate-smart agriculture implementation? A case study in Cauca, Colombia. Issue 3 (15th March 2020) - Osorio-García, A. M.; Paz, L.; Howland, F.; Ortega, L. A.; Acosta-Alba, I.; Arenas, L.; Chirinda, N.; Martinez-Baron, D.; Bonilla Findji, O.; Loboguerrero, A. M.; Chia, E.; Andrieu, N.
ABSTRACT: The main purpose of this work was analyzing how an innovation platform can foster and provide a basis for multi-actor collaboration in order to enable climate-smart agriculture (CSA) implementation at the local level. Using a mix of social (interactions between stakeholders, knowledge changes, adoption of practices) and technical indicators (income, fulfillment of caloric requirements of the household, farm resource use, planned biodiversity or greenhouse gas emission changes), we monitored the collaboration between an NGO, local civil authorities, associations, and farmers that aimed to achieve a common goal linked to the participatory and contextualized development of CSA in Colombia. We found that multiple stakeholder engagements led to improved interactions between members of the platform and their local environment, a proactive participation in the platform meetings and a significant increase in farmer knowledge levels on the challenges posed by climate change and the resultant extreme events. The platform also facilitated the adoption of best-bet practices that contribute towards CSA when farmers both diversify their production and decrease the use of mineral fertilizers. Our findings suggest that innovation platforms can facilitate the collective understanding and use of CSA options corresponding to local conditions and priorities.